Osteohistology of the Scapulocoracoid of Confuciusornis and Preliminary Analysis of the Shoulder Joint in Aves - Wu, Qian; Bailleul, Alida M.; Li, Zhiheng; O’Connor, Jingmai; Zhou, Zhonghe (Frontiers in Earth Science, 2021)
As key components of the tetrapod pectoral girdle, the scapula and coracoid have played a significant role in the evolution of forelimb locomotion among terrestrial vertebrates. The transition from a fused scapulocoracoid in ancestral non-avian theropods to a presumably more flexible separated scapula-coracoid in early birds is considered to be one of the key morphological transitions related to the rapid refinement of flight. In most Mesozoic birds (e.g., Enantiornithes and Ornithuromorpha) and crown birds the scapula and coracoid are separate, with few exceptions (e.g., flightless paleognaths). In contrast, in Confuciusornis, a basal pygostylian from the Early Cretaceous Jehol Biota, the scapula and coracoid remain plesiomorphically fused. This raises questions regarding the influence of shoulder girdle architecture on the early evolution and refinement of avian flight. The paravian scapula-coracoid joint has never previously been investigated using histology, thus jointist morphology has only been inferred superficially. In order to better understand the evolution of this joint in Mesozoic birds, we make the first histological study of the scapulocoracoid glenoid joint in Confuciusornis. The results demonstrate that the scapula and coracoid both consist of cancellous and compact bone, with both fibrolamellar and parallel-fibered structure. A thin layer of calcified cartilage is present on the glenoid fossa surface, representing remnants of the articular surface for the humerus. Both histology and computed tomography reveal that the scapulocoracoid of Confuciusornis is fully fused, forming a synostosis. Humeral histology suggests the studied individual was nearing completion of its first year of growth, suggesting the Confuciusornis scapulocoracoid fused before skeletal maturity was achieved, as in flightless paleognaths, whereas in the plesiomorphic condition fusion occurs late in ontogeny. We hypothesize the fused scapulocoracoid of Confuciusornis is secondarily evolved and suggest the primary factor responsible for this morphology may have been a decrease in mechanical stimulation at the glenoid of Confuciusornis relative to other volant birds, linked to the unique flight style of this taxon. Further investigation into the histology of the glenoid joint in other Mesozoic paravians and extant birds will help to clarify the morphological transition of the scapula-coracoid joint in early avian evolution.